HANDICRAFT PRODUCT DESIGN FOR MICRO AND SMALL ENTERPRISES IN MALANG TOURISM (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Malang City has 77,778 MSMEs and 141,906 workers in various business sectors, one of which is a Handicraft. Micro and small enterprises in this city are known to have good and quality products, but there are still many of these MSEs who still have to struggle in the design of their products. The existing problem is that there has not been handicraft product design special for micro and small enterprises in Malang Tourism. The method used in this study was focus group discussion activity which was done with the handcrafters of Malang handcrafters association. The research has produced the handicraft product designs for MSEs in this city. The designs are the use of the word Malang on the product; use of the picture of the town’s monument; picture of lion’s head and lotus as symbol of the town; beautiful; sharp color; unique and dynamic impression; functional aspect of the product; easy to carry; and light.